Gamified Project-Based Learning Strategy to Enhance Students’ Collaboration and Creativity Skills: A Quasi-Experimental Study at Al-Islam Junior High School Krian Sidoarjo - Bandono, Adi; Sabariah, Sabariah; Rufii, Rufii; Tardjo, Netty; Tafuzi, Novta Ittaqy; Sufairo, Nurus; Nugroho, Sukmo Hadi (Rekayasa, 2025)
This study examines the effectiveness of a Gamified Project-Based Learning (PjBL) strategy in enhancing students’ collaboration and creativity skills at SMP Al-Islam Krian Sidoarjo. Although PjBL has been widely implemented to foster 21st-century competencies, challenges remain in sustaining student motivation and engagement during project activities. Gamification through point systems, badges, levels, rewards, and leaderboards offers a potential solution by integrating game elements that stimulate student participation and intrinsic motivation. This study employed a mixed-methods approach with a quasi-experimental non-equivalent control group design. A total of 35 respondents were divided into two groups: an experimental group receiving gamified PjBL and a control group receiving conventional PjBL. Data were collected through pre-test and post-test instruments (using a Likert scale of 1–5), observation sheets, student interviews, and rubric-based project assessments. The findings demonstrate a significant increase in collaboration and creativity among students in the experimental group. Quantitative results reveal large effect sizes for both collaboration (d = 1.42) and creativity (d = 1.57), with p 0.001. In contrast, the control group showed only marginal improvements. Qualitative evidence from observations and interviews further indicates heightened engagement, stronger team communication, and increased idea generation among students exposed to gamified PjBL. The study contributes theoretically by enriching the discourse on the integration of gamification in PjBL environments and practically by offering empirical insights for secondary schools seeking to develop more interactive, student-centered pedagogical strategies. The findings underscore the potential of gamified PjBL as a transformative instructional model for cultivating essential 21st-century skills in Indonesian middle schools.